Effectiveness Of The Kangaroo Method In Reducing Fever After Dpt1 Immunization In Infants Aged 2-4 Months - Anis Riyanti; Raden Maria Veronika Widiatrilupi (Jurnal Maternitas Kebidanan, 2026)
DPT1 immunization is an important basic immunization that protects infants from diphtheria, pertussis, and tetanus. Despite its benefits, DPT1 immunization may cause side effects, including fever, which can lead to discomfort in infants and concern among parents. Kangaroo Mother Care (KMC), a skin-to-skin contact method between mother and infant, is a non-pharmacological intervention that promotes thermoregulation, comfort, and physiological stability in infants. This study aimed to determine the effectiveness of the kangaroo method in reducing fever following DPT1 immunization among infants aged 2–4 months. A quantitative approach was employed using a quasi-experimental design with a pretest-posttest group design. The study involved 20 infants who received DPT1 immunization and were selected through purposive sampling. The data were analyzed using univariate and bivariate analyzes with SPSS version 25. The Wilcoxon Match Pairs Test was used to assess differences in body temperature before and after the intervention. The findings revealed a significant reduction in body temperature following the application of the kangaroo method, with a p-value of 0.000 (<0.05). These results indicate that the kangaroo method is effective in reducing fever after DPT1 immunization in infants aged 2–4 months. Therefore, KMC can be considered a safe, simple, and effective non-pharmacological intervention for managing post-immunization fever in infants.